2018
DOI: 10.2355/isijinternational.isijint-2017-705
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Si Addition on Oxidation Behavior of Nb Containing Ferritic Stainless Steel

Abstract: The effect of Si on the oxidation resistance of high purity Nb containing 19% Cr ferritic stainless steels has been investigated by means of isothermal heating at temperatures up to 1 273 K in air and, the structures of the scale and scale/metal interface were investigated with FE-SEM and FE-TEM. The results are as follows: Si improved the oxidation resistance, as reported in previous studies. The Si addition of about 0.1% improved the limit temperature of the oxidation resistance more than 100 K. The presence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…Also, it was suggested that grain-refining owing to Ti addition was due to the presence of Ti at Cr 2 O 3 grain boundaries interrupting the transportation of Cr 2 O 3 grain boundaries in lateral direction. The same mechanism was reported in one of our previously published papers 9) for Mn addition. The thickening of the Cr 2 O 3 scale by the addition of Ti was attributed to the following mechanism.…”
Section: Effect Of Ti Addition On Scale Formationsupporting
confidence: 81%
See 1 more Smart Citation
“…Also, it was suggested that grain-refining owing to Ti addition was due to the presence of Ti at Cr 2 O 3 grain boundaries interrupting the transportation of Cr 2 O 3 grain boundaries in lateral direction. The same mechanism was reported in one of our previously published papers 9) for Mn addition. The thickening of the Cr 2 O 3 scale by the addition of Ti was attributed to the following mechanism.…”
Section: Effect Of Ti Addition On Scale Formationsupporting
confidence: 81%
“…9(II), the internal oxidation phase consisted of ª-Al 2 O 3 . In our previously published papers, 9,10) we mentioned that when Nb-containing ferritic stainless steels which also contained small amounts of Al were oxidized in air, the internal Al-containing oxidized phase consisted of ª-Al 2 O 3 , not ¡-Al 2 O 3 . Those results were in agreement with the findings of this study where we used Nb-free steels.…”
Section: Fe-tem Observationsmentioning
confidence: 99%
“…This should not be surprising, since niobium is an excellent oxygen getter [15]. However, the amount of niobium oxide is too small to be detected by XRD and its formation may have been caused by a small amount of gas trapped among mixed starting powders and into the powder compact in the die/punch set-up when the temperature reached values above 600 ºC during sintering [27]. The highest and lowest densities for all of the disc samples was obtained for P1250 and R1150, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have reported the beneficial effect of some elements as Si and Mo, in improving the properties of metals and alloys. Inoue et al (2018) reported that an adequate amount of Si addition to stainless steel could promote the formation of SiO2 layer at the substrate/oxide interface. The formed SiO2 can also act as the nucleation site for the formation of Cr2O3 scales (Nikrooz et al, 2012).…”
Section: Introductionmentioning
confidence: 99%